American foreign policy since world war II - Hook, Steven W., 1959- (CQ Press, 2013)
The classic text on American foreign policy, Hook and Spanier's book has long set the standard in guiding students through the complexities of the field. Giving students the historical context they need, the book allows them to truly grasp the functions and frequent dysfunctions of the nation's foreign policy agenda.